Development of potential antiviral strategy against coxsackievirus B4 - Tan, E.L.; Wong, A.P.Y.; Poh, C.L. (Elsevier, 2010)
Coxsackievirus B4 (CVB4) can cause a broad range of diseases such as aseptic meningitis, meningoencephalitis, myocarditis, hepatitis, pancreatitis, gastroenteritis, necrotizing enterocolitis, pneumonia and sudden death in the neonates. CVB4 has also been implicated as a possible etiological agent for type 1 insulin dependent diabetes mellitus (IDDM). In this study, the possibility of RNA interference (RNAi) as a potential therapeutic approach to treat CVB4 infection was explored. The results showed that the Rhabdomyosarcoma (RD) cells treated with 19-mer siRNAs displayed high specificity against CVB4 replication without displaying any sign of target effects. The siRNA targeting the 3C(Pro) region of CVB4 genome was also established to be the most effective in inhibition of CVB4 replication in RD cell line in a dosage dependent manner, indicating its potential to be developed as an antiviral strategy against CVB4. (C) 2010 Elsevier B.V. All rights reserved.